Theorizing inquiry in the moral space of practice. Issue 2 (3rd April 2017) - Yanchar, Stephen C.; Slife, Brent D.
ABSTRACT: Moral realism has been advanced as a central theme in contemporary hermeneutic thought. From this standpoint, participation in cultural practices is made possible and meaningful by ontologically real moral goods and reference points. Cultural practices thus constitute a moral referential totality for human action. This article suggests that these and related hermeneutic insights offer a unique perspective for taking account of practical involvement in the world and can form the basis of an interpretive frame for research that foregrounds this practice-based moral realism. An emphasis on moral realist concepts such as participation in practice, distinctions of worth, strong evaluations, and moral reference points can allow interrelated phenomena to show up as aspects of a moral ecology and reveal something about their moral significance within a form of practice. Moreover, inquiry of this sort can reveal something about that form of practice as a space of moral possibilities for action.